Biorhythm Analysis Of The Analgesic Effect Of Paracetamol In Inpatients With COVID-19 At The Hospital - Yuneka Saristiana; Fendy Prasetyawan; Adiyansyah Lukman Hakim; Althaf Rajahala B Sinun; Deo Rudita Febrian Waly (Journal Health of Indonesian, 2024)
The global COVID-19 pandemic has posed unprecedented challenges to global health, impacting healthcare institutions worldwide. Dr. Soedomo Regional General Hospital in Trenggalek has been actively involved in treating COVID-19 patients, emphasizing the need for improved care standards and effective symptom management. Paracetamol, a commonly used medication, is a key focus in this endeavor. This study investigates the chronopharmacology of paracetamol in COVID-19 patients, emphasizing the importance of timing in therapeutic interventions. The research, conducted at Dr. Soedomo Regional General Hospital, involves 100 COVID-19 patients undergoing paracetamol therapy. The analysis includes demographic data, paracetamol administration at different times, and the resulting body temperature changes. The findings reveal that the body's response to paracetamol varies significantly depending on the time of administration. Notably, at 4:00 PM, a more pronounced decrease in body temperature is observed, suggesting a heightened effectiveness of therapy. This phenomenon is attributed to the body's circadian rhythm, influencing physiological functions over a 24-hour period. This study lays the groundwork for the "right time, right dose" concept in clinical practice. Considering the circadian rhythm is essential in designing personalized and effective treatment protocols, aiming for optimal outcomes. Despite limitations, including a small sample size, this research provides valuable insights into the circadian aspects of drug efficacy, paving the way for more tailored treatment approaches.